Oceans Apart: The Cocos Islanders’ View Of Australian Family Law - Hussain, Jamila (Journal of Malaysian and Comparative Law, 1992)
The communities of the Cocos and Christmas Islands constitute a small but unique minority in the Australian political system. The two groups of Islands are geographically remote from Australia, being about 2,800 kilometres northwest of Perth in the midst of the Indian Ocean. A substantial majority of the inhabitants on the Cocos Islands and a substantial majority on the Christmas Island are of Malay stock, speak the Malay language and profess Islam as their religion.